Assessing anxiety during the COVID-19 delta epidemic: Validation of the Chinese coronavirus anxiety scale - Lian, Qiaoping; Xia, Lu; Wu, Daxing (Frontiers in Psychology, 2022)
The study aimed to examine the psychometric properties of the Coronavirus Anxiety Scale (CAS) during the coronavirus disease 2019 (COVID-19) delta epidemic. 2,116 participants on the Chinese mainland completed the online survey. We employed exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to investigate the factor structure. The findings showed that the one-factor model of the CAS Chinese version fitted perfectly with the data. The multigroup CFAs showed the measurement invariance across gender and age groups (18 to 29 and 30 to 68). We also examined the CAS's internal consistency and convergent and concurrent validity. The results demonstrated that the one-factor model had good reliability and convergent and concurrent validity. Overall, according to our findings, the CAS Chinese version was reliable for measuring coronavirus anxiety during the COVID-19 delta outbreak.